Sustainable Environmental Management Through a Municipal Solid Waste Charging Scheme: A Hong Kong Perspective - Cheng, Cuicui; Zhou, You; Zhang, Lin (Frontiers in Environmental Science, 2022)
Municipal Solid Waste (MSW) charging is a method for waste management by charging residents a price on garbage disposal. Due to increasing amount of MSW, Hong Kong has planned to implement MSW charging scheme in 2023. This paper aims to evaluate the potential efficacy and challenges of MSW charging scheme in Hong Kong. We first summarize the experiences from Taipei and Seoul, two typical cities that have successfully implemented the charging scheme to handle MSW. Strong enforcement and good supportive resources in the two cities has led to high effectiveness in MSW management. We then provide a simple analysis on the urgency of Hong Kong MSW concern and the public attitudes on waste management. We highlight the challenges with suggestions for sustainable environmental management.